2022
DOI: 10.1038/s41380-022-01651-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel microRNA, novel-m009C, regulates methamphetamine rewarding effects

Abstract: Methamphetamine (METH) is a widely abused psychostimulant, whose hyper-rewarding property is believed to underlie its addictive effect, but the molecular mechanism regulating this effect remains unclear. We previously reported that decreased expression of a novel microRNA (miRNA), novel-m009C, is implicated in the regulation of METH hyperlocomotion. Here, we found that novel-m009C may be homologous to hsa-miR-604. Its expression is consistently downregulated in the nucleus accumbens (NAc) of mice when exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…Therefore, it is urgent to develop safe and effective therapeutic drugs. MA is a kind of psychomotor stimulant and has been reported to induce a strong rewarding effect [7]. In this study, we observed that LBP could reverse MA‐induced high CPP scores and behavioral sensitization.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Therefore, it is urgent to develop safe and effective therapeutic drugs. MA is a kind of psychomotor stimulant and has been reported to induce a strong rewarding effect [7]. In this study, we observed that LBP could reverse MA‐induced high CPP scores and behavioral sensitization.…”
Section: Discussionsupporting
confidence: 57%
“…Conditioned place preference (CPP) is a commonly used behavior test to evaluate the reward-effect mechanism of addictive drugs [6]. Most studies use the CPP test to study drug addiction mechanisms and screen potential drug strategies to inhibit relapse [7,8]. Prevention of drug relapse is a primary condition in the treatment of drug addiction, and it is also a research hotspot in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, non-coding RNAs (ncRNAs) have become an important biomarker for studying the pathogenesis of disease and identifying drug targets. [14][15][16][17] ncRNAs, such as miRNAs, silence gene expression by binding to mRNA, thereby affecting the function of organisms. Conversely, the long ncRNAs (lncRNAs) and circular RNAs (circRNAs) can competitively bind miRNAs as competing endogenous RNAs (ceRNAs) to regulate the downstream gene expressions, which plays a positive role in disease treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, non‐coding RNAs (ncRNAs) have become an important biomarker for studying the pathogenesis of disease and identifying drug targets 14–17 . ncRNAs, such as miRNAs, silence gene expression by binding to mRNA, thereby affecting the function of organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In the eld of drug addiction, conditioned place preference(CPP) is an effective and commonly used method to verify drug dependence status through behavioral changes in animals [38,39]. Changes in CPP caused by MA abuse can be mapped to multiple brain regions such as the nucleus accumbens [40], hippocampus [41], and hypothalamus [42], and are also associated with changes in the trends of addiction-related neurotransmitters such as dopamine and glutamate [43,44]. Based on the above evidence, we hypothesize that exercise can modulate the metabolic homeostasis of the MA-induced brain.…”
Section: Introductionmentioning
confidence: 99%